Menstrual irregularities, fertility status, and ovarian function in female patients with leprosy in India. (11th July 2014) - Khanna, Neena; Singh, Manjula; Rasool, Seemab; Ammini, Ariachery; Bhatla, Neerja; Garg, Vijay; Rao, Sunder; Bhattacharya, Sambit Nath
Abstract Background Gonadal involvement in males in lepromatous leprosy is not uncommon, but there is a paucity of literature on the involvement of gonads in female patients with leprosy. This study was undertaken to determine if there is any menstrual dysfunction, alteration in fertility status and circulating luteinizing hormone (LH), follicle‐stimulating hormone (FSH), prolactin, and estradiol in female patients with paucibacillary (PB) and multibacillary (MB) leprosy. Materials and methods In a cross‐sectional study, 229 patients with leprosy (79 with PB leprosy and 150 with MB leprosy) and 100 age‐matched non‐leprosy controls were evaluated for menstrual function, fertility status, and circulating sex hormones. Results Twenty percent of patients with MB leprosy had menstrual irregularities post‐dating the onset of leprosy in comparison to 6.3% patients with PB leprosy, and this difference was statistically significant (P < 0.001). However, the fertility profile of patients with PB leprosy was comparable to that of patients with MB leprosy (P > 0.05). A significantly higher number of patients with MB leprosy (9.3%) had elevation of circulating FSH, LH, and prolactin vis‐à‐vis patients with PB leprosy (1.3%), and this difference was statistically significant (P < 0.05). Similarly, the mean levels of LH, FSH, and prolactin were significantly elevated in patients with MB leprosy vis‐à‐vis patients with PB leprosy and controls (P < 0.05). Conclusions Multibacillary leprosy may be associated with menstrual irregularities and elevation of gonadotropin hormones, indicating an ovarian dysfunction.